Incentives facing UK-listed companies to comply with the risk reporting provisions of the UK Corporate Governance Code. (15th November 2016) - Klumpes, P.; Ledlie, C.; Fahey, F.; Kakar, G.; Styles, S.
Abstract: Recent changes made to the UK Corporate Governance Code require UK firms to report new or enhanced narrative information concerning their principal risks, their risk management processes and their future viability. This paper analyses whether the level and nature of voluntary compliance with these new requirements is consistent with alternative economic and political visibility incentives. We analyse relevant sections of financial reports produced by industry-matched samples of large-, mid- and small-cap UK-listed firms during the transitional 2013–2014 financial reporting years. Both specific and generic readability attributes of the reports are measured. We find that virtually no firm in our sample has provided any viability statement. Empirical analysis of disclosures concerning principal risk assessment and review processes appear to be primarily motivated by political visibility reasons. Examples of particularly good and cases of poor corporate risk reporting practices are also discussed. Possible implications for the actuarial profession are discussed.